Markers of angiogenesis in patients with rheumatoid arthritis depending on its clinical characteristics - E. B. Komarova (Современная ревматология)
The level of vascular endothelial growth factor (VEGF) and the assessment of synovial vascularization can reflect the intensity of angiogenic processes that are an important step in the initiation and chronicity of rheumatoid arthritis (RA).Objective: to study the blood level of VEGF and to assess the degree of synovial vascularization in patients with RA depending on the duration of the disease and the degree of its activity and on the level of anti-cyclic citrullinated peptide (anti-CCP) antibodies.Patients and methods. A total of 173 patients (women, 85%; men, 15%; mean age, 47.7±10.22 years; mean disease duration, 3.82±3.43 years) diagnosed with RA underwent Doppler ultrasonography of the hand joints with assessment of the intensity of synovial vascularization and determination of blood VEGF concentrations by enzyme immunoassay (BCM Diagnostic, Canada).Results. In patients with RA duration less than 2 years, the blood level of VEGF was 30% higher and the synovial vascularization scored 3 was 4 times more common than in those with longer RA durations. In RA patients with high disease activity, blood VEGF concentrations were 2 times higher and the synovial vascularization scored 3 was observed 6 times more often than in those with low RA activity. In patients with the blood level of anti-CCP antibodies over 60 U/ml was 1.5-fold higher and the synovial vascularization score of 2–3 was twice more frequently than in those who were lowly positive for anti-CCP antibodies. High VEGF levels and synovial hypervascularization may be markers for the severe clinical course of RA and for its high progression rate, as well as for the development of early joint destruction.